Wireless Data Acquisition of Transient Signals for Mobile Spectrometry Applications. Issue 5 (May 2016) - Trzcinski, Peter; Weagant, Scott; Karanassios, Vassili
Wireless data acquisition using smartphones or handhelds offers increased mobility, it provides reduced size and weight, it has low electrical power requirements, and (in some cases) it has an ability to access the internet. Thus, it is well suited for mobile spectrometry applications using miniaturized, field-portable spectrometers, or detectors for chemical analysis in the field (i.e., on-site). There are four main wireless communications standards that can be used for wireless data acquisition, namely ZigBee, Bluetooth, Wi-Fi, and UWB (ultra-wide band). These are briefly reviewed and are evaluated for applicability to data acquisition of transient signals (i.e., time-domain) in the field (i.e., on-site) from a miniaturized, field-portable photomultiplier tube detector and from a photodiode array detector installed in a miniaturized, field-portable fiber optic spectrometer. These are two of the most widely used detectors for optical measurements in the ultraviolet–visible range of the spectrum. A miniaturized, 3D-printed, battery-operated microplasma-on-a-chip was used for generation of transient optical emission signals. Elemental analysis from liquid microsamples, a microplasma, and a handheld or a smartphone will be used as examples. Development and potential applicability of wireless data acquisition of transient optical emission signals for taking part of the lab to the sample types of mobile, field-portable spectrometry applications will be discussed. The examples presented are drawn from past and ongoing work in the authors' laboratory. A handheld or a smartphone were used as the mobile computing devices of choice.